Anticipatory postural adjustments during an archery performance - Na, J.-Y.; Ryu, D.; Ko, J.-H. (European Journal of Sport Science, 2024)
The present study investigated whether there is an anticipatory postural adjustment (APA) prior to the onset of predictable perturbation generated by a releasing in the archery performance task. Eighteen volunteers were divided into two groups (expert vs. novice) depending on skill levels. Participants stood on a force plate holding a bow with a laser pointer and took a full drawing motion aiming the laser pointer to the center of target, placed 10 m away from the force plate, then released motion was performed based on the individual's preferred timing. Motion capture system measured the bow motion in 3D, two force plates estimated center of pressure (COP) displacements, and electromyographic (EMG) recorded eight lower limb muscles during the anticipatory and compensatory phases of postural control. The results revealed that, compared to the novice group, (1) the expert group showed smaller variability of bow motion, (2) the APA patterns of the COP and muscle activities before the onset of perturbation (releasing), and (3) shorter time interval between the perturbation onset and the COP peak displacement. The findings suggest that a long-term practice results in the experts could be adopted to use APA generating mechanical benefit to compensate for predictable perturbation. This would be able to lead to a more stable subsequent postural control to realize the task goal.